A Longitudinal Assessment of Perceived Discrimination and Maladaptive Expressions of Anger Among Older Adults: Does Subjective Social Power Buffer the Association?. (2nd September 2016) - Lee, Yeonjung; Bierman, Alex
Abstract: Objectives: We examine whether perceived discrimination in older adults is associated with external conflict (anger-out) and internally directed anger (anger-in), as well as how subjective social power—as indicated by a sense of personal control and subjective social status—modifies these associations while holistically controlling for time-stable confounds and the five major dimensions of personality. Method: The 2006 and 2008 psychosocial subsamples of the Health and Retirement Study were combined to create baseline observations, and the 2010 and 2012 waves were combined to create follow-up observations. Responses were analyzed with random-effects models that adjust for repeated observations and fixed-effects models that additionally control for all time-stable confounds. Results: Discrimination was significantly associated with anger-in and anger-out. Fixed-effects models and controls for personality reduced these associations by more than 60%, although they remained significant. Measures of subjective social power weaken associations with anger-out but not anger-in. Discussion: The mental health consequences of perceived discrimination for older adults may be over-estimated if time-stable confounds and personality are not taken into account. Subjective social power can protect victims of discrimination from reactions that may escalate conflict, but not from internalized anger that is likely to be wearing and cause further health problems.